Odpowiedź :
Odpowiedź:
[tex]\begin{cases}2(x+2)-(y-1)=5\\3x+2y=7\end{cases}\\\\\\\begin{cases}2x+4-y+1=5\\3x+2y=7\end{cases}\\\\\\\begin{cases}2x+5-y=5\\3x+2y=7\end{cases}\\\\\\\begin{cases}2x-y=5-5\\3x+2y=7\end{cases}\\\\\\\begin{cases}2x-y=0\\3x+2y=7\end{cases}\\\\\\\begin{cases}-y=-2x\ \ /\cdot(-1)\\3x+2y=7\end{cases}\\\\\\\begin{cases}y=2x\\3x+2y=7\end{cases}[/tex]
[tex]3x+2\cdot2x=7\\\\3x+4x=7\\\\7x=7\ \ /:7\\\\x=1\\\\y=2\cdot1=2\\\\\\\begin{cases}x=1\\y=2\end{cases}\\\\\\Sprawdzenie\\\\\begin{cases}2(1+2)-(2-1)=5\\3\cdot1+2\cdot2=7\end{cases}\\\\\\\begin{cases}2\cdot3-1=5\\3+4=7\end{cases}\\\\\\\begin{cases}6-1=5\\7=7\end{cases}\\\\\\\begin{cases}5=5\\7=7\end{cases}[/tex]
Para liczb x=1 , y=2 jest rozwiązaniem układu równań ponieważ spełnia oba równania